Deterioration of Cortical and Trabecular Microstructure Identifies Women With Osteopenia or Normal Bone Mineral Density at Imminent and Long‐Term Risk for Fragility Fracture: A Prospective Study. (10th December 2019) - Chapurlat, Roland; Bui, Minh; Sornay‐Rendu, Elisabeth; Zebaze, Roger; Delmas, Pierre D.; Liew, Danny; Lespessailles, Eric; Seeman, Ego
ABSTRACT: More than 70% of women sustaining fractures have osteopenia or "normal" bone mineral density (BMD). These women remain undetected using the BMD threshold of −2.5 SD for osteoporosis. As microstructural deterioration increases bone fragility disproportionate to the bone loss producing osteopenia/normal BMD, we hypothesized that the structural fragility score (SFS) of ≥70 units, a measure capturing severe cortical and trabecular deterioration, will identify these women. Distal radial images were acquired using high‐resolution peripheral quantitative tomography in postmenopausal French women, mean age 67 years (range 42–96 years); 1539 women were followed for 4 years (QUALYOR) and 561 women followed for 8 years (OFELY). Women with osteopenia or normal BMD accounted for 80% of fractures. Women ≥70 years, 29.2% of the cohort, accounted for 39.2% to 61.5% of fractures depending on follow‐up duration. Women having fractures had a higher SFS, lower BMD, and a higher fracture risk assessment score (FRAX) than women remaining fracture‐free. In each BMD category (osteoporosis, osteopenia, normal BMD), fracture incidence was two to three times higher in women with SFS ≥70 than <70. In multivariable analyses, associations with fractures remained for BMD and SFS, not FRAX. BMD was no longer, or weakly, associated with fractures after accounting for SFS, whereas SFS remained associated with fracture after accounting for BMD. SFS detected two‐to threefold more women having fractures than BMD or FRAX. SFS in women with osteopenia/normal BMD conferred an odds ratio for fracture of 2.69 to 5.19 for women of any age and 4.98 to 12.2 for women ≥70 years. Receiver‐operator curve (ROC) analyses showed a significant area under the curve (AUC) for SFS, but not BMD or FRAX for the women ≥70 years of age. Targeting women aged ≥70 years with osteopenia indicated that treating 25% using SFS to allocate treatment conferred a cost‐effectiveness ratio < USD 21, 000/QALY saved. Quantifying microstructural deterioration complements BMD by identifying women without osteoporosis at imminent and longer‐term fracture risk. © 2019 The Authors. Journal of Bone and Mineral Research published by American Society for Bone and Mineral Research.